Validitas Pengembangan Media Pembelajaran Cerita Rakyat Berbasis Augmented Reality Materi Unsur Intrinsik Cerita Siswa Kelas IV SDN Geger 1 - Latifa Rahmasari, Salsa; Rian Damariswara; Kukuh Andri Aka (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Based on classroom observations, interview, and distribution of questionnaires at SDN Geger 1 Grade IV, a notable issue during lessons is the prevalent use of conventional media, specifically storybooks, by teachers during instructional activities. Students must re-read the story multiple times to comprehend its meaning. Due to the restricted number of books and story titles, students must take turns reading. The learning process remains passive due to inadequate utilization of varied media and suboptimal technology integration Learning activities remain passive because teachers have limited use of diverse media and have not yet optimized the use of technological media. This study aims to analyze the validity of developing the use of Augmented Reality based folk tale media in teaching intrinsic story elements to fourth-grade students at SDN Geger 1 This study employs the R&D method using the ADDIE model approach. In the data collection process, a validation questionnaire was used, conducted by subject matter experts in Indonesian language and instructional media experts. Based on the findings from the content validation results, it is stated that the Augmented Reality based folk tale media achieved a percentage of 80%, indicating a validity level classified as "valid”. Meanwhile the validity of the instructional media content obtained a percentage of 88%, which is classified as "highly valid" and deemed suitable for use as a learning. Referring to the average of both validation results, a percentage of 84% was obtained. As a result the Augmented Reality based instructional media featuring folk tales in the intrinsic story elements material has met all aspects is classified as "highly valid" and is suitable for use in the learning process.